International Prognostic Index, Type of Transplant and Response to Rituximab Are Key Parameters to Tailor Treatment in Adults With CD20‐Positive B Cell PTLD: Clues From the PTLD‐1 Trial. Issue 4 (3rd March 2015) - Trappe, R. U.; Choquet, S.; Dierickx, D.; Mollee, P.; Zaucha, J. M.; Dreyling, M. H.; Dührsen, U.; Tarella, C.; Shpilberg, O.; Sender, M.; Salles, G.; Morschhauser, F.; et al.
Abstract : Tailoring treatment by patient strata based on the risk of disease progression and treatment toxicity might improve outcomes of patients with posttransplant lymphoproliferative disorder (PTLD). We analysed the cohort of 70 patients treated in the international, multicenter phase II PTLD‐1 trial (NCT01458548) to identify such factors. Of the previously published scoring systems in PTLD, the international prognostic index (IPI), the PTLD prognostic index and the Ghobrial score were predictive for overall survival. None of the scoring systems had a considerable effect on the risk for disease progression. Age and ECOG performance status were the baseline variables with the highest prognostic impact in the different scoring systems. Baseline variables not included in the scoring systems that had an impact on overall survival and disease progression were the type of transplant and the response to rituximab at interim staging. Thoracic organ transplant recipients who did not respond to rituximab monotherapy were at particularly high risk for death from disease progression with subsequent CHOP‐based chemotherapy. Patients in complete remission after four courses of rituximab and patients in partial remission with low‐risk IPI had a low risk of disease progression. We speculate that chemotherapy might not be necessary in this patient cohort. Abstract : Analysis of the patients treated in the international, multicenter phase II PTLD‐1 trial with sequential treatment with four courses of rituximab followed by four cycles of three‐weekly CHOP suggests that tailoring treatment based on patient baseline characteristics and response to treatment at interim staging might improve outcomes of patients with posttransplant lymphoproliferative disorder even further.